2015
DOI: 10.1007/s11130-015-0479-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins and Phenolic Acids of Hybrid and Native Blue Maize (Zea mays L.) Extracts and Their Antiproliferative Activity in Mammary (MCF7), Liver (HepG2), Colon (Caco2 and HT29) and Prostate (PC3) Cancer Cells

Abstract: Blue maize is an excellent source of bioactive components such as phenolic acids and anthocyanins but when it is processed for human consumption, these compounds decrease considerably. Therefore, blue maize could be directed to produce nutraceutical extracts. The aim of this study was to evaluate the relation between anthocyanins composition of acidified and non-acidified extracts from native and hybrid blue maize genotypes and their antiproliferative effect in mammary (MCF7), liver (HepG2), colon (Caco2 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 25 publications
1
46
1
3
Order By: Relevance
“…Phenolic compounds are a heterogeneous group of compounds that are present in the vast majority of plant foods. There is epidemiological and in vitro experimental evidence associating the consumption of foods rich in phenolic compounds with a low incidence of chronic diseases, which are the leading cause of death worldwide (Bennett and others ; Mohamed ; Urias‐Lugo and others ). The main characteristics through which phenolic compounds have been reported to be bioactive are related to their antioxidant, immunomodulatory, chemopreventive, anti‐platelet aggregation and anti‐inflammatory properties (de la Lastra and Villegas ; Fraga and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are a heterogeneous group of compounds that are present in the vast majority of plant foods. There is epidemiological and in vitro experimental evidence associating the consumption of foods rich in phenolic compounds with a low incidence of chronic diseases, which are the leading cause of death worldwide (Bennett and others ; Mohamed ; Urias‐Lugo and others ). The main characteristics through which phenolic compounds have been reported to be bioactive are related to their antioxidant, immunomodulatory, chemopreventive, anti‐platelet aggregation and anti‐inflammatory properties (de la Lastra and Villegas ; Fraga and others ).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that in white and yellow corn it can be found in the forms of dimers, trimers and tetramers [51]. Other authors have reported 1.94 mg/100 g [52] of free diferulic acid in blue Mexican corn which is the most abundant in that variety ( Table 5).…”
Section: Phenolic Acids In Pigmented Cornmentioning
confidence: 94%
“…The group of non-anthocyanin flavonoids includes flavonols (rutin, isoquercetin, flavonol, morin, kaempferol, and quercetin) and flavonones (naringenin and hesperetin) [26], while the phenolic acids found in corn are protocatechuic acid, vanillic acid, syringic acid, trihydroxybenzoic acid, caffeic acid, chlorogenic acid, and p-hydroxyphenylacetic acid. Ferulic acid and p-coumaric acid are the compounds with more concentrates in corn, particularly in pigmented varieties [27,28]. Total ferulic acid content detected in kernels of white varieties with Mexican genotype has been reported as 124,053 mg of ferulic acid equivalent/100 g of sample, while pigmented varieties such as blue or red corn have reported 129,985 and 130,297 mg of ferulic acid/100 g sample, respectively [15].…”
Section: Nutraceutical Properties Of Cornmentioning
confidence: 99%
“…In 2015, Mexican researchers conducted a study with extracts of phenolic acids and blue corn anthocyanins, measuring their anticancer properties in breast, liver, colon, and prostate cancer cell lines; results indicated an antiproliferative effect in all cell lines, in which malonyl glucoside cyanidin was the anthocyanin with the greatest reduction in cell viability [28]. It has also been shown that the bioactive peptides of corn exert antitumor activity through key mechanisms such as (a) the induction of apoptosis mediated through specific proteases or caspases; strategies to overcome tumor resistance to apoptotic pathways include the activation of pro-apoptotic receptors, the restoration of p53 activity, the modulation of caspases, and the inhibition of the proteasome; (b) blocking the intermediate generation of tumors by regulating cellular mechanisms associated with cell proliferation and survival, or biosynthetic pathways that control cell growth; and (c) regulation of immune system functions, increasing the expression of antigens associated with the tumor (antigenicity) in cancer cells, activating the tumor cells for them to release warning signals that stimulate the immune response (immunogenicity), or increasing the predisposition of the tumor cells to be recognized and neutralized by the immune system (susceptibility) by means of autophagy and apoptosis [63].…”
Section: Corn and Cancermentioning
confidence: 99%